KEBERHASILAN BERSARANG BURUNG REMETUK RAWA (Gerygone magnirostris) DAN REMETUK BAKAU (G. levigaster) DI HABITAT MANGROVE DI DARWIN, NORTHERN TERRITORY, AUSTRALIA - Yeni A. Mulyani; Richard A. Noske; Ani Mardiastuti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Despite its large distribution, very few studies have been done on the reproductive ecology of the genus Gerygone, a member of the family of Australo-Papuan warblers. Mangrove Gerygone and Large-billed Gerygone use mangrove habitats for breeding in the Top End of Australia. This study attempted to reveal the nesting success of those species. Both conventional method and Mayfield method were used to calculate the nesting success. The results showed that nesting success of both species was low compared to those of other Australian passerines.Keywords: Nesting success, gerygone magnirostris, gerygone levigaster, mangrove habitat, mayfield method